Respuesta :

Answer:

(- [tex]\frac{8}{5}[/tex], [tex]\frac{46}{5}[/tex] )

Step-by-step explanation:

Given the2 equations

6 - 2x = y → (1)

14 + 3x = y → (2)

Substitute y = 14 + 3x into (1)

6 - 2x = 14 + 3x ( subtract 3x from both sides )

6 - 5x = 14 ( subtract 6 from both sides )

- 5x = 8 ( divide both sides by - 5 )

x = - [tex]\frac{8}{5}[/tex]

Substitute x = - [tex]\frac{8}{5}[/tex] into either of the 2 equations for the corresponding value of y

Substituting into (1)

y = 6 - 2(- [tex]\frac{8}{5}[/tex] ) = [tex]\frac{30}{5}[/tex] + [tex]\frac{16}{5}[/tex] = [tex]\frac{46}{5}[/tex]

solution is ( - [tex]\frac{8}{5}[/tex], [tex]\frac{46}{5}[/tex] )